Hikmah Dalam Al-Qur’an: Studi Komparasi Tafsir Al Azhar Dan Al-Misbah - Nur Habibilah, Luthfan; Romadlon, Arif Firdausi Nur; Iqbal, Ipmawan Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study compares the concept of hikmah (wisdom) as interpreted in Tafsir Al-Azhar and Tafsir Al-Misbah using a comparative-descriptive approach. The research focuses on four Qur’anic verses: Al-Baqarah [2]:129, Al-Baqarah [2]:151, Ali ‘Imran [3]:164, and Al-Jumu‘ah [62]:2. It is a library-based study, with data gathered through a literature review. The findings show that both tafsirs agree on viewing hikmah as part of the prophetic educational mission. However, they differ in emphasis and interpretation: Tafsir Al-Azhar associates hikmah with moral guidance and spiritual wisdom, while Tafsir Al-Misbah presents hikmah as religious insight, legal wisdom, and practical benefit. This study contributes to the development of comparative Qur’anic interpretation, especially within the context of Indonesian Islamic scholarship